Características estruturais e físicas de material biodegradável produzido a base de zeína e fibras de milho e bananeira - Cortes, Mônica Souza [UNESP] (2015)
The search for materials which substitute oil for the production of polymers has increased a lot in the last decade, due to the high pollution caused by its derivatives. Among several alternatives of new materials studied, zein, a protein component of corn gluten, presents great polymerization characteristics with the ability to form films with compatible roles to materials derived from petroleum, however for certain uses there is need for improvement in some mechanical and resistance properties. Corn is an agricultural product of major consumption in both human and animal food attributable to its chemical composition, which gives its derivatives important nutritional and technological functions. Brazil is the third largest producer and the second largest sector of corn processing in the country is the wet milling which aims to separate the grain in relatively pure fractions: germ (with high content of oil), fiber (from the pericarp and endosperm of the grain), starch (64%) and gluten (10%) of high protein content (formed by the glutelin, globulin, albumin and zein proteins). The banana is one of the most important fruit in the world, both as regards production and marketing, being the fourth most food product produced worldwide, after rice, wheat and corn. Brazil is the second in area planted to 7 million tons a year, producing 180-200 tons of plant residues, which may favor the proliferation of fungi difficult to control with treatment, due to high humidity incident on the plantations. The extraction of the pseudostem of banana trees can be an interesting alternative income for the hand of rural work, and can be a viable alternative for reinforcing composites. There is an emerging need to seek alternatives by using its by-products, primarily the ones of lower aggregated value such as fiber, since they have low value, and are used mainly for animal food formulations. The development of new materials using these components will add ...